Afire with gratitude : we nurture our missionary spirit - Hapita, Adora; Abreu, Myrna; Gil, Mary Irisann San; Bacerra, Analyn; Torres, Nancy; Coronel, Irene; Carandang, Floral (Sampaloc, Manila : Rex Book Store, Inc., 2016)
"This textbook is inspired by the centennial celebration of the presence of the Missionary Sisters Servants of the Holy Spirit in the Philippines. In loving and grateful response to the grace and love of the Triune God, this project was born out of the desire to form community mission-spirited individuals deeply rooted in God the Source of all being, in Jesus the Divine Word, and empowered by the Holy Spirit to witness the "Truth in Love". Unlike other materials in the market, this series focuses on the Trinitarian spiritually, developing respect for uniqueness, equality, constant communication, unity, and passion for mission. It also provides varied, meaningful, and engaging learning experiences that are formative in nature. It features learner-centered activities that will move them to live their faih concretely as active members of the community".
English text.
Keywords: Religions